KUALITAS FISIK GELATIN HASIL EKSTRAKSI KULIT SAPI DENGAN LAMA PERENDAMAN DAN KONSENTRASI ASAM KLORIDA (HCl) YANG BERBED - Rapika Rapika; Zulfikar Zulfikar; Zumarni Zumarni (Jurnal Peternakan, 2016)
Gelatin is a compound hydrolysis of collagen fibers. The purpose of this research was to determine the influence of concentration of hydrochloric acid (HCl). and soaking time on the bovine hide making toward physical quality gelatin. The materials were bovine hide, hydrochloric acid and  distilled water. Data were statistically analyzed by A Completely Random Design with factorial pattern consist two factors; hydrochloric acid concentration (3% and 5%) and soaking time (4, 8, 12 and 16 hours) with three times replications. Parameters measured were pH, gel strength, yield and viscosity. The result showed that pH,  bloom strogh, yield and viscosity, centipoise (cP) of gelatin was 2.70-4.12, 53,33-185,00 g, 18.04-37.93% and 1.49-1,79, respectively. An interaction between hydrochloric acid and soaking time significantly (P˂0.01) influence in following categories: T pH, gel strength, viscosity and yield. It is conclude that the best combination treatments is  HCl 3% and 12 hours of soaking soaking.